Marketing Syariah Pada Bisnis Batu Onyx - Muhamad Ali Tamrin (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2020)
This paper aims to find out whether the sharia marketing theory has been applied to the company UD Cahaya Onyx Tulungagung. In Islamic law when discussing the marketing process, it is not far from the concept of sharia. So that the sharia marketing process itself has a character that distinguishes it from conventional marketing principles. The characteristics of sharia marketing itself are rabbaniyah, akhlaqiyah, waqi'iyah, and insaniyah. So that if these four characteristics are carried out, the interests of producers and consumers can be bridged and both will get maximum satisfaction. Responding to the importance of realizing the character of sharia marketing, the author needs to analyze whether the characteristics of sharia marketing have been realized in UD Cahaya Onyx Tulungagung. The research method used is an empirical or sociological approach where the author uses two types of data sources, namely primary data sources and secondary data sources. Meanwhile, the analysis carried out in this study is qualitative data analysis. The results of this study show that the four characteristics of Sharia marketing have been applied in business activities at UD Cahaya Onyx Tulungagung.